Synchronous tumor: colon cancer and liposarcoma - Limaylla, Himerón (2013)
This is a case report of a 58 year-old male born in Junin. Patient was referred to the emergency room from a rural hospital and was admitted with the diagnosis of intestinal obstruction. He had colicky type diffuse abdominal pain, abdominal distention, nausea and vomiting for 7 days. He had presented abdominal pain off and on for the past 2 months. Pain was severe at least 3 to 4 times a week, improved spontaneously but returned with increased frequency, exacerbated by food ingestion, and associated with decreased appetite and 6 to 7 kg weight loss. Patient did not have any significant past medical or surgical history. During hospitalization abdominal CT showed two tumors, one in the ascending colon and the other in the retroperitoneal region. These were surgically removed. Pathology result reported well differentiated colon adenocarcinoma and dedifferentiated liposarcoma, both with surgical borders clean of neoplasia. Simultaneous finding of these tumors has not been described in the medical literature.